2019
DOI: 10.14527/pegegog.2019.036
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mathematical literacy and visual math literacy self-efficacy perceptions of middle school students

Abstract: In this study, the levels of mathematical literacy and visual math literacy self-efficacy perceptions of middle school students and the relationship between them were investigated. For this aim, the study was desgined as a correlational research model. The study group was determined according to convenience sampling. 328 middle school students (5th, 6th, 7th, and 8th graders) participated in this study with this sampling. In order to collect data, first, “Mathematical Literacy Scale” was developed. It was seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
1
0
4
Order By: Relevance
“…Ini berisi penggunaan konsep dan fungsi matematika dengan berpikir secara matematis (OECD, 2013). Di luar matematika sekolah, literasi matematis yang berarti memahami dan mengkomunikasikan pemikiran yang ditulis dalam bahasa matematika yang menjadi tingkat kognitif yang dimiliki orang untuk mengenali masalah matematika dan mengungkapkan masalah tersebut melalui cara matematika (Katranci & Şengül, 2019). Literasi matematis menyokong peserta didik untuk mengerti fungsi dan penggunaan matematika dalam aplikasi seharihari (Yuliyani & Setyaningsih, 2022).…”
Section: Aksioma: Jurnal Program Studi Pendidikan Matematikaunclassified
“…Ini berisi penggunaan konsep dan fungsi matematika dengan berpikir secara matematis (OECD, 2013). Di luar matematika sekolah, literasi matematis yang berarti memahami dan mengkomunikasikan pemikiran yang ditulis dalam bahasa matematika yang menjadi tingkat kognitif yang dimiliki orang untuk mengenali masalah matematika dan mengungkapkan masalah tersebut melalui cara matematika (Katranci & Şengül, 2019). Literasi matematis menyokong peserta didik untuk mengerti fungsi dan penggunaan matematika dalam aplikasi seharihari (Yuliyani & Setyaningsih, 2022).…”
Section: Aksioma: Jurnal Program Studi Pendidikan Matematikaunclassified
“…Matematika merupakan ilmu abstrak dan universal yang tersusun secara terstruktur serta mencakup analisis kemungkinan-kemungkinan pola yang terdapat dalam suatu bilangan dan ruang (Altun, 2008;Katranci & Şengül, 2019). Makna yang terkandung dalam matematika dapat digunakan secara luas dengan mempelajari konsep dan aturan matematika (Aksu & Koruklu, 2015).…”
Section: Pendahuluanunclassified
“…Makna yang terkandung dalam matematika dapat digunakan secara luas dengan mempelajari konsep dan aturan matematika (Aksu & Koruklu, 2015). Hal ini dapat terjadi karena adanya kemampuan literasi matematika (Katranci & Şengül, 2019).…”
Section: Pendahuluanunclassified
“…Gatabi et al found that Iranian ninth grade math textbooks contained significantly fewer questions related to math literacy, diversity of content, and opportunities for students to participate in mathematical modeling than those in Australia [19]. Yasemin et al believe that teachers' effective use of mathematical language and their enrichment of visual materials in the curriculum can help improve middle school students' mathematical literacy and visual mathematical literacy self-efficacy, and there is a high degree of positive correlation between mathematical literacy and visual mathematical literacy [20]. Guzel et al found a significant positive correlation between math literacy and math self-efficacy, and a substantial relationship between the interest in, enjoyment of, anxiety about math, and the subject climate of mathematics courses [21].…”
Section: Introductionmentioning
confidence: 99%